Kapłan sługą miłosierdzia. Refleksja moralno-pastoralna w kontekście Nadzwyczajnego Jubileuszu Miłosierdzia (8 grudnia 2015 – 20 listopada 2016) - Kluz, Marek (Poznańskie Studia Teologiczne, 2016)
The Extraordinary Jubilee of Mercy announced in the bull Misercicordiae vultus by the Holy Father Francis, becomes an opportunity to reflect on the priestly vocation in the context of the truth about mercy. The practice of authentic mercy is a fundamental task of priestly life. In this perspective it seems that the mercy as the style of the priestly life requires to be presented again with new enthusiasm and with renewed pastoral activity. This is a key task for the Church. Therefore, the moral-pastoral reflections included in this publication aim to - in the light of the documents of the Church, especially the writings and statements of popes: John Paul II, Benedict XVI and Francis - encourage in the Holy Year to rediscover and revive the sense of identity and essential tasks of priestly ministry fulfilled primarily in preaching and practicing the virtue of mercy.